2015
DOI: 10.1016/j.jallcom.2015.03.211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pr3+ substitution on the microstructure, specific surface area, magnetic properties and specific heating rate of Ni0.5Zn0.5Pr Fe2−O4 nanoparticles synthesized via sol–gel method

Abstract: xia. (2015) Effect of Pr3+ substitution on the microstructure, specific surface area, magnetic properties and specific heating rate of Ni0.5Zn0.5PrxFe2−xO4 nanoparticles synthesized via sol-gel method. Journal of Alloys and Compounds,. Permanent WRAP URL:http://wrap.warwick.ac.uk/94091 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…It should be mentioned that the observed particle size is somehow larger than the crystallite size obtained from the XRD study due to the formation of connecting necks between the two neighboring particles during calcination. No large aggregated nanoparticles are observed confirming much higher degree of dispersion as compared with a nontemplated synthesis method [37]. Due to this fact, the specific area of the Ni0.5Zn0.5Fe2O4 microtubes was considerably enhanced in this study.…”
Section: Please Insertsupporting
confidence: 49%
“…It should be mentioned that the observed particle size is somehow larger than the crystallite size obtained from the XRD study due to the formation of connecting necks between the two neighboring particles during calcination. No large aggregated nanoparticles are observed confirming much higher degree of dispersion as compared with a nontemplated synthesis method [37]. Due to this fact, the specific area of the Ni0.5Zn0.5Fe2O4 microtubes was considerably enhanced in this study.…”
Section: Please Insertsupporting
confidence: 49%
“…The magnetothermal effect can increase the local temperature of magnetic catalysts resulting in enhancing the kinetics of OER [112]. In addition, composite magnetic catalysts can generate heat locally under AC magnetic field due to the internal flip of spins relative to the crystalline lattice (Néel relaxation) thereby increasing catalyst temperature [113][114][115][116]. Recent studies have revealed that structurally stable catalysts can undergo spin-state flipping changes by applying magneto-thermal perturbations using AMF, without altering their structure.…”
Section: Effect Of An External Magnetic Fieldmentioning
confidence: 99%
“…[ 19 ] Yan and his co‐workers reported that adding Pr 3+ ions in Ni–Zn ferrite reduces the average crystallite size and enhances specific surface area sixfold, exploring its catalytic applications. [ 20 ] Pr substitution in hexaferrite systems is reported to reduce the electron exchange between Fe 2+ and Fe 3+ ions at octahedral sites affecting their electrical properties. [ 21 ] Talebi et al explored potential photocatalytic applications under UV radiation of Co–ferrite when doped with Pr 3+ ions.…”
Section: Introductionmentioning
confidence: 99%